The reflective cracking in thin surfacings - Pais, Jorge C. (1998)
This paper shows a laboratory study on reflection cracking in thin surfacings, where the reflective cracking take an important point in pavement life, undertaken with the Reflective Cracking Device and the Crack Activity Meter. The Crack Activity Meter was used to measure load associated differential vertical and horizontal movement between the two sides of a crack in cracked pavements before overlay. The crack movements after overlay were calculated with a finite element model. The Reflective Cracking Device used with the shear machine, introduced by SHRP program, was employed to simulate in laboratory the crack activity patterns measured in the field.